PENGARUH ATRIBUT PRODUK DAN MUTU PRODUK TERHADAP DAYA TARIK PRODUK SEPATU CONVERSE DI TUNJUNGAN PLAZA SURABAYA - Sari Handajani (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2018)
In line with the rapid development of the economy, more and more products are offered in the market to meet the needs of consumers. Thus the quality of the product or the good quality of service will every consumer will love the product with the best quality, performance, and innovative complement. Based on this, it can be said that marketing is the spearhead of the company's overall operations. The products offered by manufacturers and purchased by consumers are to meet the expected needs. Therefore, consumers will be interested in choosing or buying goods that can meet their expectations. Buying interest is a fully planned desire by consumers to make real purchases. Briefly the purchase interest can be interpreted as a purchase plan. Each company is expected to be able to develop its products to be more quality, have competitive prices, good distribution channels and other advantages so that the products offered are truly products that meet the needs that consumers want. This research aims to find out the Effect of Product Quality On Product Attractiveness, Product Attributes On the Attractiveness of Converse Shoe Products.The data used in this study is primary data obtained by distributing questionnaires to consumers who visit and are interested in buying at Converse outlets in Tunjungan Plaza Surabaya. The analysis technique used is multiple linear regression. Test results show that Product Quality has a positive influence on product attractiveness. Product Attributes have a positive influence on product attractiveness.